Thomas Mann, Doctor Faustus - Beddow, Michael (Landmarks of world literature, 1994)
In Doctor Faustus, his last major novel, Thomas Mann attempted to interpret and judge Germany's role in European culture and history since the Reformation. Through the figures of the solitary avant-garde composer, Adrian Leverkühn, and his often bemused biographer Serenus Zeitblom, Mann explores Germany's self-understanding and self-assertion. The novel intermingles fiction and history in a narrative that combines complex psychological analysis, virtuoso stylistic parody and vivid evocation of atmosphere and milieu. Michael Beddow analyses the structure of the plot and explores the significance of its chief historical, theological, psychological and musical themes. He considers Mann's understanding and modification of the Faust tradition, his thematic and formal indebtedness to Nietzsche and his interest in Adorno's neo-Marxism. The study concludes with an account of the work's generally hostile reception in defeated Germany